2012
DOI: 10.1175/jcli-d-11-00562.1
|View full text |Cite
|
Sign up to set email alerts
|

Realism of Rainfall in a Very High-Resolution Regional Climate Model

Abstract: The realistic representation of rainfall on the local scale in climate models remains a key challenge. Realism encompasses the full spatial and temporal structure of rainfall, and is a key indicator of model skill in representing the underlying processes. In particular, if rainfall is more realistic in a climate model, there is greater confidence in its projections of future change.In this study, the realism of rainfall in a very high-resolution (1.5 km) regional climate model (RCM) is compared to a coarser-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
529
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(570 citation statements)
references
References 40 publications
38
529
0
3
Order By: Relevance
“…A comparison of the results for the three resolutions in Fig. 13 confirms the results shown in Kendon et al (2012). Figure 14 illustrates the performances of individual models using Taylor diagrams of the 75th, 95th, and 99th percentile values against the reference.…”
Section: Precipitation Biasessupporting
confidence: 71%
See 2 more Smart Citations
“…A comparison of the results for the three resolutions in Fig. 13 confirms the results shown in Kendon et al (2012). Figure 14 illustrates the performances of individual models using Taylor diagrams of the 75th, 95th, and 99th percentile values against the reference.…”
Section: Precipitation Biasessupporting
confidence: 71%
“…We then examine the spatio-temporal characteristics of rainfall exceeding this percentile, the absolute value of which will differ between different datasets. The advantage of this approach is that it removes the effects of bias in precipitation amounts between the different datasets, while retaining reliable information about precipitation pattern and behavior (Kendon et al 2012). Here we calculate the 75th, 95th and 99th percentile of daily precipitation probability distribution function (PDF) at each grid point for June-August (JJA) of each year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bên cạnh đó, rất nhiều nghiên cứu trong nước và quốc tế đã được thực hiện nhiều nghiên cứu về ảnh hưởng của sự thay đổi độ phân giải, thay đổi các sơ đồ tham số hóa đối lưu đến chất lượng mô phỏng. Các nghiên cứu trước đây đã chỉ ra rằng có độ phân giải cao hơn có thể mô phỏng thực tế hơn hoàn lưu khí quyển quy mô lớn cũng như phân bố lượng mưa toàn cầu và khu vực (Buonomo và [3][4][5][6][7][8][9][10]. Như vậy đối với bài toán dự báo mưa nói chung hay dự báo mưa ảnh hưởng do bão nói riêng, việc hạ độ phân giải và thay đổi sơ đồ tham số hóa đối lưu là cần thiết.…”
Section: Mở đầU *unclassified
“…The expected further increase in computational resources will presumably mean a further increase in RCM resolution, leading to the use of nonhydrostatic RCMs. Kendon et al (2012) reported on a recent study showing results from dynamical downscaling with a non-hydrostatic RCM at 1.5 km grid spacing.…”
Section: Developing and Extending Rcmsmentioning
confidence: 99%